Gold nanoparticle enhanced electrochemical impedance sensor for Human Papillomavirus (HPV) 16 detection using synthetic target - Ainun Solehah Amrul Muhadi (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To determine surface modification on interdigitated electrodes (IDE) for DNA immobilization process. To construct immobilization of modified probe of high risk HPV strains (16) interdigitated electrodes (IDE) by the electrode. To produce validation by electrical test on selectivity and sensitivity test will be conducted using in-vitro clinical sample for electrical characterization.